Correlation of TET2 SNP rs2454206 with improved survival in children with acute myeloid leukemia featuring intermediate‐risk cytogenetics. Issue 8 (26th June 2018) - Wang, Xingjuan; Chen, Xi; Yang, Zhenzhen; Dou, Hu; Lu, Ling; Bi, Junqin; Zou, Lin; Yu, Jie; Bao, Liming
Abstract: Single nucleotide polymorphisms (SNPs) may influence the disease course and outcome of hematologic neoplasms. SNP rs2454206 is common in the TET2 gene, which plays a role in epigenetic regulation of myelopoiesis. Few investigations examined the role of TET2 SNP rs2454206 in acute myeloid leukemia (AML) and none of those studies was performed in Chinese populations. Here, we report the prevalence and clinical relevance of TET2 SNP rs2454206 in 254 Chinese patients with childhood AML. Our data demonstrate that TET2 SNP rs2454206 AG/GG is associated with improved overall survival and event‐free survival in AML patients with intermediate‐risk cytogenetics features. The prognostic impact of TET2 SNP rs2454206 AG/GG was independent of other common AML risk factors, such as age, white blood cell count, and FLT3‐ ITD. No difference in TET2 expression levels in AML with TET2 SNP rs2454206 AA and TET2 SNP rs2454206 AG/GG was detected, indicating that TET2 SNP rs2454206 status does not affect TET2 expression in pediatric AML.